Capillary refill time as part of an early warning score for rapid response team activation is an independent predictor of outcomes. (August 2020) - Sebat, Christian; Vandegrift, Mary Anne; Oldroyd, Sean; Kramer, Andrew; Sebat, Frank
Abstract: Background: Capillary refill time (CRT) is easy, quick to perform and when prolonged in critical illness, correlates with progression of organ failure and mortality. It is utilized in our hospital's early warning score (EWS) as one of 11 parameters. We sought to define CRT's value in predicting patient outcomes, compared to the remaining EWS elements. Methods: Five-year prospective observational study of 6480 consecutive Rapid Response Team (RRT) patients. CRT measured at the index finger was considered prolonged if time to previous-color return was >3 s. We analyzed the odds ratio of normal vs prolonged-CRT, compared to the other EWS variables, to individual and combined outcomes of mortality, cardiac arrest and higher-level of care transfer. Results: Twenty-percent ( N = 1329) of RRT-patients had prolonged-CRT (vs normal-CRT), were twice as likely to die (36% vs 17.8%, p < .001), more likely to experience the combined outcome (72.1% vs 54.2%, p < .001) and had longer hospital length of stays, 15.3 (SD 0.3) vs 13.5 days (SD 0.5) ( p < .001). Multivariable logistic regression for mortality ranked CRT second to hypoxia among all 11 variables evaluated ( p < 001). Conclusions: This is the first time CRT has been evaluated in RRT patients. Its measurement is easy to perform and proves useful as an assessment of adult patients at-risk for clinical decline. Its prolongation in our population was an independent predictor of mortality and the combined outcome. This study and others suggest that CRT should be considered further as a fundamental assessment of patients at-risk for clinical decline.